Neighboring Molecular Engineering in Diels–Alder Chemistry Enabling Easily Recyclable Carbon Fiber Reinforced Composites - Gu, Song; Xiao, Yan‐Fang; Tan, Shi‐Huan; Liu, Bo‐Wen; Guo, De‐Ming; Wang, Yu‐Zhong; Chen, Li (Angewandte Chemie International Edition, 2023)
Although a variety of dynamic covalent bonds have been successfully used in the development of diverse sustainable thermosetting polymers and their composites, solving the trade‐off between recovery efficiency and comprehensive properties is still a major challenge. Herein, a “one‐stone‐two‐birds” strategy of lower rotational energy barrier (Er) phosphate‐derived Diels–Alder (DA) cycloadditions was proposed for easily recyclable carbon fiber (CF)‐reinforced epoxy resins (EPs) composites. In such a strategy, the phosphate spacer with lower Er accelerated the segmental mobility and dynamic DA exchange reaction for network rearrangement to achieve high‐efficiency repairing, reprocessing of the EPs matrix and its composites and rapid nondestructive recycling of CF; meanwhile, incorporating phosphorus‐based units especially reduced their fire hazards. The resulting materials simultaneously showed excellent thermal/mechanical properties, superb fire safety and facile recyclability, realizing the concept of recycling for high‐performance thermosetting polymers and composites. This strategy is of great significance for understanding and enriching the molecular connotation of DA chemistry, making it potentially applicable to the design and development of a wide range of dynamic covalent adaptable materials toward practical cutting‐edge‐tech applications. A strategy of tailoring dynamic covalent bonds with a low rotational energy barrier was proposed to fabricate phosphate‐derived Diels–Alder crosslinked recyclable thermosets and their composites, simultaneously overcoming the trade‐off between recycling efficiency and comprehensive properties in current covalent adaptable materials and offering a guidance for the rational design of sustainable thermosetting polymers for versatile applications.